Potential biomarkers for the diagnosis of respiratory tract infection and lungs cancer - Khan, Khushbukhat; Aslam, Muhammad Adeel; Zahra, Fatima Tuz; Basheer, Hamid; Bilal, Muhammad; Sumrin, Aleena (Cellular and Molecular Biology, 2017)
Major hurdle faced by many physicians in treating various respiratory tract infections and lung carcinomas is their late or mis-diagnosis. In most respiratory tract infections the manner of infection is not completely understood. Similarly, various lung carcinomas are diagnosed at advance stages at which not only the treatment possibilities are narrowed but the chances of survival are also reduced. So, for the sake of better treatment, the quick and improved diagnostic strategies are suggested. Protein biomarkers fully fit the description in this regard as they have shown great potential in specific diagnosis of many respiratory diseases and also have shown capability in timely pin pointing different stages of lung carcinomas. Many serum biomarkers are presently being used for diagnosis but the efficiency for diagnosis of these biomarkers is lower when used alone. So, physicians are suggested to use the combination of different biomarkers. Moreover, genetic biomarkers are also currently studied to indicate the exact stage of disease, the possible damage occurred, the severity of disease and also for the analysis of the possible body response to the therapeutics.